DAMPAK KEBERADAAN TEMPAT PEMBUANGAN AKHIR TERHADAP KONDISI LINGKUNGAN DAN SOSIAL DI MASYARAKAT (STUDI KASUS DESA KARANG REJO KOTA METRO LAMPUNG) - Diyan Ahmad Saputra; Agus Setiawan; Endro P. Wahono; Gunardi Winarno (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2020)
Open Dumping and inadequate landfill management and waste management have negative impacts on the community. Failure to manage waste in Metro City is not only due to technical weaknesses, lack of financial support, inefficient management agencies, and inappropriate systems can cause Emotional Mental Disorders (GME) as well as densely populated settlements, slums, poor ventilation, damaged house buildings, damp and moldy walls of houses, to the presence of pests around the house can cause anxiety to mental disorders. Researchers evaluated the presence of landfills in 23 Karang Rejo Metro cities, so that the existence of landfill can be in accordance with the prevailing rules. The research method used is qualitative, researchers decipher words in the opinion of respondents descriptively. In addition to interviews, to strengthen the data sought, researchers took pictures and made observations to the community with inter-community interactions, how people live environmental and social lives. Garbage disposal technology has developed, one of the development of the waste disposal method is the Sanitary Landfill method, with the Reusable Sanitary Landfill (RSL) model. The way the supply method works is that the garbage is stacked in a land, then the garbage can is compacted as a ground liner. Ground liners are coated with geomembranes, this layer that will withstand the pervasiveness of lindi into the soil and contaminate groundwater. On top of the geomembrane layer is another geotextile that serves to hold the dirt so that it does not mix with lindi water. The limitations of perspective in the study because the study lies in the small sample, it is suggested it is necessary to do more research by comparing some cases with different concepts.